Science and Technology Behind Nanoemulsions - Karakuş, Selcan (IntechOpen, 2018)
This book covers new micro-/nanoemulsion systems in technology that has developed our knowledge of emulsion stability. The emulsion system is a major phenomenon in well-qualified products and has extensive usages in cosmetic industry, food industry, oil recovery, and mineral processes. In this book, readers will find recent studies, applications, and new technological developments on fundamental properties of emulsion systems.